Active control of the hybridization effect of near-field coupled resonators in metamaterial for a tunable negative refractive index at terahertz frequencies. (September 2021) - Hien, Nguyen Thi; Ca, Nguyen Xuan; Khuyen, Bui Xuan; Van Huynh, Tran; Khiem, Nguyen Sy; Tung, Nguyen Thanh; Lam, Vu Dinh; Tung, Bui Son
Abstract: To achieve broadband negative refraction, which is useful for many practical applications, recent studies have shown that the use of hybridization is one of the most effective methods. Nevertheless, reported studies often propose changing structural parameters rather than external factors. In this article, a method to control actively the bandwidth of negative refractive index (NRI) metamaterials based on second-order hybridization operating in the terahertz regime is proposed numerically by use of a simple disk-grid dimer. By use of the semiconductor InSb as the metallic component, the conductivity is tunable according to temperature, which changes the separation of magnetic resonant frequencies in second-order hybridization scheme and the plasma frequency of metamaterial. Consequently, the fractional bandwidth of the double-NRI region is extended. The mechanism of the phenomenon is explained clearly by both calculations and simulation. Finally, the fractional bandwidth of the NRI region was optimized by variation of the dielectric thickness of the disk-grid monomer and the thickness of the interlayer between the two monomers. The optimal fractional bandwidth is 10.4%, with a high transmitted power of 94% and a high figure of merit of 52.9 at 1.68 THz. Our results pave the way for the implementation of diverse semiconductors in tunable broadband NRI metamaterials at terahertz frequencies. Highlights: We numerically study a terahertz thermotunable hybridization broadband NRI metamaterial. The tunability is achieved by use of resonators made of InSb with a temperature-dependent carrier density. Τhe thermally increased carrier density of InSb is the main mechanism for the enhanced magnetic resonance. Tunable broadband negative refractive index hybridization with good attributes was realized.